Portion Control: A Key to Weight Management - Cassie C. Gaisser; Karla P. Shelnutt; Lori Johnson; Annie Wallau (EDIS)
Portion sizes and overall calorie intake in the United States have significantly increased over the last 50 years. Along with this increase in calories, portion sizes have grown larger over the years. Understanding portion control can help you eat the right amount of food to maintain a healthy weight. Written by Cassie C. Gaisser, Karla P. Shelnutt, Lori Johnson, and Annie Wallau, and published by the UF/IFAS Department of Family, Youth and Community Sciences, revised March 2024.